Peritoneal Dialysis Catheter Position Evaluated by Ultrasound: Can it Replace Abdomen X-Ray in Patients Presenting Catheter Misplacement? - Zeiler, Matthias; Zanoli, Luca; Scarfia, Rosalia Viviana; Santarelli, Stefano; Granata, Antonio (Ultraschall in der Medizin - European Journal of Ultrasound, 2017)
Background Malfunction of the peritoneal dialysis catheter is frequently caused by dislocation. The diagnostic approach is classically based on abdomen X-ray together with detailed case history and physical examination. Despite being rarely applied in clinical practice to evaluate catheter misplacement, ultrasound is a noninvasive, radiation-free technique that is potentially useful also to explore reasons for catheter malfunction. Consequently, we aimed to evaluate the diagnostic accuracy of ultrasound to identify peritoneal catheter misplacement.Methods In a multicenter observational blinded study, we compared ultrasound to abdomen X-ray for catheter localization in 93 consecutive peritoneal dialysis patients with dialysate outflow problems enrolled in two nephrology and dialysis units. The position of the catheter was annotated on a standard scheme of nine abdominopelvic regions. The sensitivity, specificity, positive and negative predictive value and Kappa coefficient were calculated.Results Dislocation out of the inferior abdominopelvic regions was present in 19 patients (20 %) at X-ray and 23 patients (25 %) at ultrasound. Correct determination of the position of the catheter in the lower abdomen by ultrasound had a sensitivity of 93 % (95 % CI 84 – 97 %), specificity of 95 % (95 % CI 72 – 100 %), positive predictive value of 99 % (95 % CI 91 – 100 %), negative predictive value of 78 % (95 %CI 56 – 92 %) and Kappa coefficient of 0.82 (95 % CI 0.67 – 0.96). In 10 out of 93 patients (11 %), there was a position mismatch between X-ray and ultrasound in an adjacent abdominopelvic region.Conclusion Our results suggest that abdomen X-ray for the evaluation of peritoneal catheter position can be replaced by ultrasound in experienced hands. This bedside diagnostic procedure might reduce costs, the time necessary for diagnosis and lifetime radiation exposure.
Keywords: ultrasound; peritoneal dialysis; catheters; malfunction; radiography